2012
DOI: 10.3892/ijo.2012.1473
|View full text |Cite
|
Sign up to set email alerts
|

Expression and role of nestin in human cervical intraepithelial neoplasia and cervical cancer

Abstract: Nestin expression reportedly correlates with aggressive growth, metastasis, poor prognosis and presence of cancer stem cells (CSCs) in various tumors. In this study, we determined the expression and role of nestin in cervical intraepithelial neoplasia (CIN) and cervical cancer. We performed immunohistochemical and in situ hybridization analyses of nestin in 26 cases for each stage of CIN and 55 cervical cancer tissue samples. To examine the role of nestin in cervical cancer cells, we stably transfected express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Inhibition of nestin in pancreatic cancer cells does not alter cell differentiation [17]. We reported previously that shRNA that targets nestin suppresses sphere formation by melanoma cells [32], while overexpression of nestin induces increased sphere formation by cervical cancer cells [70]. We observed the same results using pancreatic cancer cell lines, but there have been no reports describing correlations between nestin expression levels and the tumor formation ratio using the dilution method in immunodeficient animals.…”
Section: Nestin In Pancreatic Cancer Stemnesssupporting
confidence: 65%
“…Inhibition of nestin in pancreatic cancer cells does not alter cell differentiation [17]. We reported previously that shRNA that targets nestin suppresses sphere formation by melanoma cells [32], while overexpression of nestin induces increased sphere formation by cervical cancer cells [70]. We observed the same results using pancreatic cancer cell lines, but there have been no reports describing correlations between nestin expression levels and the tumor formation ratio using the dilution method in immunodeficient animals.…”
Section: Nestin In Pancreatic Cancer Stemnesssupporting
confidence: 65%
“…We herein isolated sphere-forming cells derived from the cervical cancer cell line, SiHa (HPV16-positive squamous cell carcinoma), according to the standard protocol for sphere formation using a low-attachment plate and serum-free media [23]. A representative microscopic picture showed that several sphere-forming, but not monolayer cells were observed on the low-attachment plate (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, recent research has characterized nestin as a cancer stem cell marker in various cancers; these include brain tumors, ovarian, head and neck, prostate, and pancreatic cancers (26)(27)(28)(29)(30). Nestin has also been implicated in pancreas development and pancreatic cancer progression (30).…”
Section: Introductionmentioning
confidence: 99%